2017
DOI: 10.3892/mco.2017.1289
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the NSD3‑BRD4‑CHD8 pathway in pelvic high‑grade serous carcinomas of tubo‑ovarian and endometrial origin

Abstract: Abstract. Identification of novel therapeutics in pelvic high-grade serous carcinoma (HGSC) has been hampered by a paucity of actionable point mutations in target genes. The aim of the present study was to investigate the extent of amplification of the therapeutically targetable NSD3-CHD8-BRD4 pathway in pelvic HGSC, and to determine whether amplification is associated with worse prognosis. The Cancer Genome Atlas (TCGA) ovarian and endometrial cancer cohorts were retrospectively analyzed via online data-minin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
(41 reference statements)
5
13
0
Order By: Relevance
“…These preclinical data with JQ1 and GS-626510 in primary ovarian cancer cell lines and xenografts confirm and expand the results of recent in-tumor shRNA genetic screens revealing c-MYC overexpression as a therapeutic target in chemotherapy-resistant tumors through the use of BRD4 inhibitors (27,28). While previous studies have found that some ovarian tumors may contain BRD4 amplifications and that such tumors may respond to BET inhibition (29), the prevalence of these amplifications in ovarian cancer tends to be low (30). Our data did not show any significant point mutations or CNVs in any BET genes, suggesting that the activity of JQ1 and GS-626510 in our tumor models was most likely related to c-MYC amplification that may be targetable by BET inhibition along with BRD4 amplifications.…”
Section: Discussionsupporting
confidence: 80%
“…These preclinical data with JQ1 and GS-626510 in primary ovarian cancer cell lines and xenografts confirm and expand the results of recent in-tumor shRNA genetic screens revealing c-MYC overexpression as a therapeutic target in chemotherapy-resistant tumors through the use of BRD4 inhibitors (27,28). While previous studies have found that some ovarian tumors may contain BRD4 amplifications and that such tumors may respond to BET inhibition (29), the prevalence of these amplifications in ovarian cancer tends to be low (30). Our data did not show any significant point mutations or CNVs in any BET genes, suggesting that the activity of JQ1 and GS-626510 in our tumor models was most likely related to c-MYC amplification that may be targetable by BET inhibition along with BRD4 amplifications.…”
Section: Discussionsupporting
confidence: 80%
“…40 Here, we observed an increase in alanine and aspartate levels on overexpression of both NSD3s and Pdp3, which may be related to increased glutamine metabolism. NSD3 amplification is found in different types of cancers, such as leukemia, [46][47][48] breast, 7,46-49 bladder, [46][47][48] lung, [46][47][48] endometrium, 50 ovary, 50 and head and neck. 44,45 The metabolomics profile of NSD3s + and Pdp3 + is similar; however, not identical, indicating that each protein acts by regulating a common core of metabolic pathways in addition to a handful of other proteinspecific reactions.…”
Section: Discussionmentioning
confidence: 99%
“…BRD4 recruits different kinds of transcriptional regulators to acetylated chromatin and organizes super-enhancers (Sabari et al, 2018). BRD4 interacts with histone modifiers such as JMJD6 and NSD3 and chromatin remodelers such as CHD4 to facilitate transcription initiation (Jones and Lin, 2017;Konuma et al, 2017;Liu et al, 2013;Shen et al, 2015;Zhang et al, 2016). BRD4 also binds to the positive transcription elongation factor b (P-TEFb) and promotes transcription elongation (Jang et al, 2005;Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%